Osteopenia and Total Disc Prosthesis Subsidence: Inclusion/Exclusion Criteria for Total Disc Replacement - Lee, Casey K. (SAS J, 2007)
BACKGROUND: Prosthetic subsidence is an adverse event of disc arthroplasty with a total disc prosthesis. Factors affecting prosthetic subsidence are (1) the size of the prosthetic endplate (footprint), (2) amount of load applied to the spine, and (3) compressive strength of the vertebral bone. The size of the prosthetic endplate has been addressed adequately in the development of the current generation of total disc prostheses. However, little information is available on the relation between osteopenia (low bone mineral density [BMD]) and prosthetic subsidence. We evaluated the relation between osteopenia and compressive strength of vertebral bone and propose an inclusion/exclusion guideline for disc arthroplasty in the presence of osteopenia. METHODS: This study was based on previously published data by C.K. Lee on bone mineral density, contact surface area, and applied load that emphasized the critical contact surface area required to prevent subsidence. The study included 35 cadaveric vertebral bones (representing ages 38–68) that were evaluated via quantitative computed tomography for BMD and subjected to nondestructive and destructive tests for compressive strength of the vertebral bones. The relationship of osteopenia to prosthetic subsidence was evaluated from the data. RESULTS: Patients with average BMD (0.137 g/cm(3)) require a minimum contact surface area of 6.5 cm(2) for the physiologic load of 2500 N. Patients with a BMD of up to 1 SD below the average will require 9.1 cm(2) of contact area for the same load. Patients with a BMD of up to 2 SD below the average will require 13 cm(2) of contact area. DISCUSSION: The average endplate surface area of small disc prostheses is about 6.5–8 cm(2), which is enough to tolerate normal physiologic load for patients with normal BMD. Patients with BMD of 2 SD below the average will require a disc prosthesis with an endplate surface area greater than 12.75 cm(2) to tolerate normal physiologic load. The largest size of prosthetic endplate of the currently available disc prostheses is about 11 cm(2); therefore, patients with BMD below 2 SD will have a high risk of subsidence, and these patients should be excluded for disc arthroplasty. Patients with BMD between –1.5 SD and –2.0 SD may be included for disc arthroplasty only when they can receive the large size of prosthesis with greater than 10.5 cm(2) prosthetic endplates. CONCLUSIONS: All patients should be evaluated preoperatively with BMD measurement. Patients with a BMD of up to 1.5 SD below the average can be included for total disc arthroplasty. Patients with BMD of 2 SD below the average should be excluded for total disc arthroplasty, and patients with BMD of 1.5–2 SD below the average should be carefully evaluated for the appropriate size of the prosthesis prior to the surgery.